Hubungan Dukungan Keluarga dengan Kualitas Hidup Lanjut Usia Pasca Stroke di Wilayah Kerja Puskesmas Gajahan Surakarta - Octaviani, Reni; , H.M. Abi Muhlisin, SKM., M.Kep (2017)
Increasing in the number of elderly poses problems in various aspects of life. One of them is the health aspect. In elderly decreased in structure and function of organs so that elderly are susceptible to various diseases. Stroke is a disease that is common in elderly. Impact caused by stroke, among others, the inability to perform activities independently. Stroke survivors become dependent on other people around them. This leads to decreased their quality of lives. Family support is important in the healing process and recovery of the disease. Support families are able to increase confidence and motivation in the face of problems that occur. The purpose of this study to determine the relationship of family support with the quality of life in after stroke elderly in Puskesmas Gajahan Surakarta. The study design was descriptive correlative with cross-sectional approach. Sample of 46 respondents using purposive sampling technique. Data collection tools were used that interview guide family support and quality of life after stroke. Processing data using Spearman Rank. The results showed 54.3% of respondents got a good family support. Respondents who have a high quality of life and respondents who have lower quality of life have the same amount (50%). There is correlation of family support and quality of life in after stroke elderly with p value of 0.000. Researchers suggested to the family to further optimize the provision of family support in order to improve the quality of life of the elderly after stroke.